Signal sampling and storage applications in digital systems maintenance - Echevarria, Antonio N. (1987)
The oscilloscope, as a major tool in maintaining digital equipment, fails to provide stable, useful displays when monitoring unrepetetive, or single-shot digital sequences. A microprocessor-based, 8-data-channel device for sampling and storing these digital signals, synchronously or otherwise, at different sampling rates is proposed and implemented as a solution to this maintenance problem.
Typescript.
Thesis (M.S. Electrical Engineering)--University of the Philippines, Diliman.
Keywords: Electronic digital computers -- Maintenance and repair; Cathode rayoscillos; Maintainability (Engineering).